2016
DOI: 10.3171/2015.6.jns15674
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers as predictors of long-term outcome in severe traumatic brain injury: analysis from a randomized placebo-controlled Phase II clinical trial

Abstract: abbreviatioNs AUC = area under the curve; BBB = blood-brain barrier; DAI = diffuse axonal injury; Eg = estrogen; FIM = functional independence measure; GCS = Glasgow Coma Scale; GFAP = glial fibrillary acidic protein; GOS = Glasgow Outcome Scale; ICP = intracranial pressure; IL = interleukin; IQR = interquartile range; NGF = nerve growth factor; NSE = neuron-specific enolase; Pg = progesterone; ROC = receiver operating characteristic; sTBI = severe traumatic brain injury; TNF-a = tumor necrosis factor-a. Pg])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
(76 reference statements)
1
46
0
1
Order By: Relevance
“…Commercial or custom made enzyme-linked immunosorbent assays (ELISAs) were used in some studies (21, 34, 35, 40, 42, 44, 49, 52, 57, 61, 67, 68, 77, 81, 85, 86, 91), as well as other techniques (or not mentioned in the text) (36, 51, 55, 66, 69, 71), even if a majority used clinically available assays such as the (C)LIA-mat system from Sangtec/DiaSorin (7, 11, 18, 3739, 41, 43, 4548, 50, 53, 54, 56, 5860, 6265, 70, 7276, 7880, 8284, 8790, 92–95). In general, ELISA samples showed less volatility over time (42, 49, 68, 81, 91).…”
Section: Resultsmentioning
confidence: 99%
“…Commercial or custom made enzyme-linked immunosorbent assays (ELISAs) were used in some studies (21, 34, 35, 40, 42, 44, 49, 52, 57, 61, 67, 68, 77, 81, 85, 86, 91), as well as other techniques (or not mentioned in the text) (36, 51, 55, 66, 69, 71), even if a majority used clinically available assays such as the (C)LIA-mat system from Sangtec/DiaSorin (7, 11, 18, 3739, 41, 43, 4548, 50, 53, 54, 56, 5860, 6265, 70, 7276, 7880, 8284, 8790, 92–95). In general, ELISA samples showed less volatility over time (42, 49, 68, 81, 91).…”
Section: Resultsmentioning
confidence: 99%
“…Three small, single-center clinical studies have now shown positive outcomes with low-dose i.m. PROG (Xiao et al, 2008;Mofid et al, 2016;Raheja et al, 2016), but large phase III clinical trials using i.v. administration at much higher doses of the hormone had negative results (Wright et al, 2007(Wright et al, , 2014Skolnick et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Further, three small, single-center clinical studies using lowdose intramuscular (i.m.) PROG have shown positive outcomes (Xiao et al, 2008;Mofid et al, 2016;Raheja et al, 2016). HBC has been used clinically (Preskorn, 2005;Mermelstein et al, 2013) as a vehicle for i.m.…”
Section: Introductionmentioning
confidence: 98%
“…The relation of the NSE level in serum with outcome has been shown in 72 h postinjury, probably because of its short half-life (29). The increase in the serum level of NSE was associated to favorable outcome in other study (30). However, previous (19) and present studies indicate that the serum level of NSE is not different between patients with favorable outcome and those with unfavorable outcome.…”
Section: Discussionmentioning
confidence: 49%